Mal Goode reporting : the life and work of a Black broadcast trailblazer - Tsoukas, Liann E. (Liann Elias) (University of Pittsburgh Press, 2024)
The First Comprehensive Biography on a Barrier-Breaking Black Radio and Television Newscaster.